2012
DOI: 10.23986/afsci.4806
|View full text |Cite
|
Sign up to set email alerts
|

Potential and limitations of phosphate retention media in water protection: A process-based review of laboratory and field-scale tests

Abstract: The application of phosphorus (P)-sorbing materials offers a possible solution for treating municipal wastewater and agricultural runoff. In this paper we discuss P retention and release mechanisms, and review studies on the P retention of different materials and their use as reactive media in filter beds. The main mechanisms for P retention are sorption on metal (mostly Fe or Al) hydroxide surfaces and, in alkaline conditions, the formation of Ca-P precipitates. The retention of P is strongly affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Therefore, adsorption might be more significant phosphate removal mechanism in aerated systems since no white precipitates were visible in the filters. The adsorption follows inner-sphere ligand exchange mechanism [15] where they reacted by forming monodentate and bidentate complexes which were determined by how they were coordinated [16].…”
Section: 2mentioning
confidence: 99%
“…Therefore, adsorption might be more significant phosphate removal mechanism in aerated systems since no white precipitates were visible in the filters. The adsorption follows inner-sphere ligand exchange mechanism [15] where they reacted by forming monodentate and bidentate complexes which were determined by how they were coordinated [16].…”
Section: 2mentioning
confidence: 99%
“…Thus treatment wetlands are also often constructed on drained 47 such as slags have been frequently tested, because they are widely available and cheap 73 materials. However, based on Klimeski et al (2012) review, P sorption tests are usually 74 conducted using water with a high P concentration, whereas the average P concentrations 75 in peat extraction runoff are 80-90 μg Ptot L -1 and 25-30 μg PO4-P L -1 (Postila et al, 2014; 76 Tuukkanen et al, 2012). 77 78 Addition of Fe, Al and Ca can increase PO4-P retention due to their sorption capacity 79 (Richardson, 1985;Seo et al, 2005).…”
Section: Introduction 37mentioning
confidence: 99%
“…The materials may also be classified according to their chemical composition as follows: those containing metals (mostly Fe and Al), those containing soluble divalent earth metals (Ca, Mg), and mixtures of the two [12]. Several studies have shown that some materials are capable of removing P from household wastewater or agricultural runoff, but more studies are needed to optimize the design of filter beds intended for field conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…While P appears in inorganic and organic forms under field conditions, laboratory experiments mostly use inorganic P. Secondly, sufficient contact time between the filter material and the flow solution is likewise a crucial point in developing P filters [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation